2022
DOI: 10.3389/feduc.2022.894142
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Digital Skills of Early Childhood Teachers Through Online Science, Technology, Engineering, Art, Math Training Programs in Estonia

Abstract: Teacher professional development programs, including mid- and long-term Science, Technology, Engineering, Art, Math (STEAM) courses, have recently moved from in person learning at university premises to an online environment. Whether it is a temporary change in learning methods caused by the COVID-19 restrictions or whether it will become a new normal is currently under discussion in many teacher training institutions around the world. The aim of this study was to design and implement time- and money-saving sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
0
5
0
2
Order By: Relevance
“…Aydin-Gunbatar et al (2020 support the thesis and assert that the training processes develop skills such as communication, teamwork, creativity, and interdisciplinary integration. Leoste et al (2022), also share this idea and suggest that the training programs provide the necessary knowledge for interdisciplinary integration. Therefore, these programs are aimed at imparting training in STEM teaching competencies.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Aydin-Gunbatar et al (2020 support the thesis and assert that the training processes develop skills such as communication, teamwork, creativity, and interdisciplinary integration. Leoste et al (2022), also share this idea and suggest that the training programs provide the necessary knowledge for interdisciplinary integration. Therefore, these programs are aimed at imparting training in STEM teaching competencies.…”
Section: Discussionmentioning
confidence: 84%
“…Two significant aspects to analyze in program implementation are modality and training duration. Although the majority of analyzed programs were conducted in-person, Ciftci and Topcu (2022), Leoste et al (2022), andPewkam andChamrat (2022) argue that virtual or blended environments provide a more flexible and adaptive training approach that caters to the individual needs of participants. However, according to Wu et al (2019Wu et al ( , 2021 these training environments create a significant workload for both work and learning, as many virtual tools are overwhelming and at times impractical, leading to usability and integration inadequacies.…”
Section: Discussionmentioning
confidence: 99%
“…In science learning, students learn to collect data, analyze information, and build arguments based on valid evidence. In this process, students must also understand how to access information ethically and responsibly (Leoste et al, 2022) Information is easily found and accessed via the internet in the digital era. However, information found on the internet may only sometimes be reliable or may not be copyrighted.…”
Section: Resultsmentioning
confidence: 99%
“…According to Leoste, Lavicza, Fenyvesi, Tuul and Õun [48], the mechatronics kit can be regarded as a digital educational toy, STEAM kit, and device supporting STEAM teaching and learning approaches. Participants in the conducted research were briefed and introduced to the type of kit during the "Technical Education in Primary Education" course, a didactics program that focuses on suitable methodological approaches for teaching "Technical Education" in primary school.…”
Section: Mechatronics Kit In Education Of Future Primary Education Te...mentioning
confidence: 99%